Design and Implementation of an Integrated e-Commerce Application for Electronics Stores - Yopie, Yopie Hidayat; Widyarto, Setyawan (Proceedings of the Informatics Conference, 2026)
The e-commerce industry has become an integral part of global trade, including the sale of electronic devices. While traditional sales methods still dominate, inefficiencies such as limited market reach and operational inefficiencies persist. This research aims to develop and implement an integrated e-commerce application for electronics stores to enhance sales efficiency and effectiveness. A case study approach was adopted, employing interviews, surveys, and observations to collect data, which was then analyzed using qualitative and quantitative methods. The results demonstrate that the developed e-commerce application successfully met functional and non-functional requirements, including user registration, product search, shopping cart, payment, data security, performance, and scalability. The system utilizes Laravel for backend development, Vue.js for frontend, and a MySQL database hosted on an Ubuntu NGINX server. Integration with Midtrans payment gateway and Raja Ongkir shipping services ensures secure and efficient transaction processes. System evaluation revealed significant improvements in response time and user satisfaction. This application not only enhances the efficiency and effectiveness of electronic sales but also provides a superior shopping experience for users. This research makes a significant contribution to the electronics industry and suggests developing additional features and market expansion in the future.